Efektivitas Campuran Metolachlor dan Pendimethalin Terhadap Gulma di pertanaman Kedelai (Glycine max L. Merril) - Baidhawi Baidhawi (Fakultas Pertanian, Universitas Syiah Kuala, 2007)
Effectiveness Mix of Metolachlor and Pendimethalin on Weed on Soybean (Glycine max L. Merril) AreaABSTRACT. Weed management is an integral part of soybean production. In order to select the most appropriate herbicide or devise the optimum weed control system, one must be able or properly identify the weed present within a field. Research was aimed to find out influence of mixture two herbicide, with under herbicide dosage to weed and yield of soybean. Field experiment was conducted on Inceptisol from February 2006 until May 2006 at station research Agriculture Faculty Padjajaran University, 700 m above sea level. The factorial experiment was carried out in randomized complete block design with two replications. The first factors-metolachlor (doses of herbicide a.i. 0,0; 0,75; 1,50; and 2,25 kg ha-1). Application showed that herbicide metolachlor and pendimethalin had single or mixture on the studied gave higher percentage of weeds covered, and weed dry matter were lower comparison. The mixture metolachlor and pendimethalin can increased dry of yield compared to herbicide single application.